The Effect of Female Sex on Hepatitis C Incidence Among People Who Inject Drugs: Results From the International Multicohort InC3 Collaborative. (24th August 2017) - Esmaeili, Aryan; Mirzazadeh, Ali; Morris, Meghan D; Hajarizadeh, Behzad; Sacks, Henry S; Maher, Lisa; Grebely, Jason; Kim, Arthur Y; Lauer, Georg; Cox, Andrea L; Hellard, Margaret; Dietze, Paul; et al.
Abstract : This study provides valuable information on differences in hepatitis C virus incidence by sex in people who inject drugs, controlling for differences in related exposures and behavioral factors, using well-characterized longitudinal data from geographically diverse prospective cohort studies. Abstract: Background: The objective of this study was to assess differences in hepatitis C virus (HCV) incidence by sex in people who inject drugs (PWID), using a large international multicohort set of pooled biological and behavioral data from prospective observational studies of incident human immunodeficiency virus (HIV) and HCV infections in high-risk cohorts (the InC3 Collaborative). Methods: HCV infection date was estimated based on a hierarchy of successive serological (anti-HCV), virological (HCV RNA), and clinical (symptoms and/or liver function tests) data. We used a Cox proportional hazards model to calculate the crude and adjusted female to male (F:M) hazard ratio (HR) for HCV incidence using biological sex as the main exposure. Results: A total of 1868 PWID were observed over 3994 person-years of observation (PYO). Unadjusted F:M HR was 1.38 (95% confidence interval [CI], 1.15–1.65) and remained significant after adjusting for behavioral and demographic risk factors (1.39 [95% CI, 1.12–1.72]). Although syringe and equipment sharing were associated with the highest HCV incidence rate in women (41.62 and 36.83 PYO, respectively), we found no sex differences attributed to these risk factors. Conclusions: Our findings indicate that women who inject drugs may be at greater risk of HCV acquisition than men, independent of demographic characteristics and risk behaviors. Multiple factors, including biological (hormonal), social network, and differential access to prevention services, may contribute to increased HCV susceptibility in women who inject drugs.